Suzuki Cello School: piano accompaniment - Suzuki, Shinichi (Suzuki Cello School, 1982)
This material is part of the worldwide Suzuki Method of teaching. Companion recordings should be used with theses publications. In addition, there are cello part books that go along with this material.